2012
DOI: 10.1177/0022034512455031
|View full text |Cite
|
Sign up to set email alerts
|

White-spot Lesions and Gingivitis Microbiotas in Orthodontic Patients

Abstract: White-spot lesions (WSL) associated with orthodontic appliances are a cosmetic problem and increase risk for cavities. We characterized the microbiota of WSL, accounting for confounding due to gingivitis. Participants were 60 children with fixed appliances, aged between 10 and 19 yrs, half with WSL. Plaque samples were assayed by a 16S rRNA-based microarray (HOMIM) and by PCR. Mean gingival index was positively associated with WSL (p = 0.018). Taxa associated with WSL by microarray included Granulicatella eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 25 publications
(40 reference statements)
3
82
2
Order By: Relevance
“…A reduced diversity and an increased prevalence of acidogenic and aciduric streptococci were evident in the untreated caries group. Similar differences have been disclosed before, but mainly in caries-active vs. caries-free infants, children or adolescents [Li et al, 2007;Aas et al, 2008;Luo et al, 2012;Tanner et al, 2012]. Our findings, based on the HOMIM technology, are in line with the concept that an ecological stress-induced imbalance of the resident microflora is involved in the caries process [Takahashi and Nyvad, 2011], and apparently, this seems true also in healthy adults with prior significant caries experience, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A reduced diversity and an increased prevalence of acidogenic and aciduric streptococci were evident in the untreated caries group. Similar differences have been disclosed before, but mainly in caries-active vs. caries-free infants, children or adolescents [Li et al, 2007;Aas et al, 2008;Luo et al, 2012;Tanner et al, 2012]. Our findings, based on the HOMIM technology, are in line with the concept that an ecological stress-induced imbalance of the resident microflora is involved in the caries process [Takahashi and Nyvad, 2011], and apparently, this seems true also in healthy adults with prior significant caries experience, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…More than 700 oral bacterial species have been identified, of which only 50% are cultivable with traditional agar-based methods [Dewhirst et al, 2010]. The bacterial profiles related to caries have been investigated with various molecular techniques [Preza et al, 2009;Luo et al, 2012;Tanner et al, 2012;Torlakovic et al, 2012]. Most studies analyzed samples collected directly from caries lesions.…”
mentioning
confidence: 99%
“…Researchers reported that S. mutans, S. wiggsiae, V. parvula, S. cristatus, F. nucleatum and A. gerencseriae are SECC-related species [28], and S. wiggsiae is effective in childhood caries both in presence and absence of S. mutans [9]. Moreover, since S. wiggsiae is highly isolated in white spot lesions and at the initiation of enamel lesions, it is thought to be efficient in initiation of caries, as well as S. mutans [29].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Consequently, orthodontic patients have an increased risk of developing gingivitis [3][4][5][6] and enamel decalcifications that can lead to white spots and caries. [6][7][8] Optimal oral hygiene requires professional instructions, adequate tools, and patient motivation, which is a crucial factor to obtain compliance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Consequently, orthodontic patients have an increased risk of developing gingivitis [3][4][5][6] and enamel decalcifications that can lead to white spots and caries. [6][7][8] Optimal oral hygiene requires professional instructions, adequate tools, and patient motivation, which is a crucial factor to obtain compliance. 9 There is no consensus in the literature regarding the effectiveness of manual vs electric toothbrushes in terms of removing plaque: a recent meta-analysis 10 concluded that there are no differences between powered and manual brushes, while in their systematic review Robinson and coworkers 11 found that only a powered toothbrush with a rotation-oscillation action reduced plaque more than a manual toothbrush.…”
Section: Introductionmentioning
confidence: 99%